(untitled) (Emerging Indexing of Global Multidisciplinary Journal, 2026)
The increasing complexity of global food systems has intensified challenges related to food adulteration, contamination, and spoilage, necessitating the development of advanced detection and monitoring technologies. This research article presents a comprehensive analysis of nanotechnology-driven approaches for food safety, focusing on nanosensors, nanobiosensors, smart packaging systems, and integrated digital frameworks. Drawing exclusively from the provided literature, the study evaluates the evolution of nanomaterials such as nanoparticles, nanofibers, nanocomposites, and quantum dots in detecting chemical contaminants, microbial pathogens, and adulterants in food matrices. The methodology involves a systematic conceptual synthesis of interdisciplinary research spanning nanotechnology, biosensing, smart product systems, and agri-food supply chain intelligence. The findings demonstrate that nanotechnology-based sensing platforms significantly enhance detection sensitivity, selectivity, and real-time monitoring capabilities compared to conventional methods. Additionally, the integration of smart connected systems and enterprise-level sensing frameworks enables proactive and data-driven food safety management. The study also highlights the role of advanced materials such as aptamer-modified nanostructures, polymeric nanochannels, and electrospun nanofibers in improving biosensor performance. Despite these advancements, challenges related to scalability, regulatory frameworks, environmental safety, and consumer acceptance remain significant. The discussion emphasizes the need for interdisciplinary collaboration, sustainable design principles, and the integration of artificial intelligence for predictive food safety systems. The study concludes that the convergence of nanotechnology, smart sensing, and digital infrastructure represents a transformative paradigm for ensuring food quality, safety, and traceability in modern agri-food systems.